# Which ordered pair is a solution of the equation 2x − y = 9 (-4,1) (-2,5) (5,1) (6,-3)

So based on my solution, the correct answer would be the third option: (5,1)

So let us try to plug in the values.

2(5) - 1 = 9

10 -1 = 9

9 = 9

So this is the correct one. Hope this answers your question.

## Related Questions

What is the range of the function f(x) = 3x2 + 6x – 9

f(x)=3x^2-6x+1

My solution is:

The domain is all real numbers--there are no restrictions like a square root or variable in the denominator

this is a U shape parabola and you want to find the bottom point, it is at the vertex

x=-b/2a =- (-6) /2 (3) =1

f(1) =3(1)^2 -6(1) +1 =3-6+1 =-2

the minimum is (1, -2)

so the range is all real numbers >= -2

By examining my solution, you could just answer the problem on your own! I hope it helps!

Solve the equation for y 2x+6y=13

2x+6y=13

Next, transfer 2x to the right side and it will look like this:

6y=13-2x

Now, divide both sides by 6, and it will look like this:

y=13-2x

--------

6

So, this is the final answer for y.

Hope this answers your question. Have a great day!

The y-coordinate of the y-intercept is the _____ term in the equation of the line.

**constant**.

I hope my answer helped you. Feel free to ask more questions. Have a nice day!

solve for x :

−3(6−2x)≥4x+12

−18+6x≥4x+12

2x≥30

x≥15

**So the answer is D ) 15 to +infinity**

I hope my answer has come to your help. God bless and have a nice day ahead!

How to solve this problem 14-6= 10-6=?

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

Algebraic terms are separated by ______. Choose all that apply. 1)= 2)+ 3)x 4)÷ 5)-

__Answer__

1)=

2)+

5)-

__Explanation__

When letter or numbers are separated by multiplication or division can be combined to make one term.

In an algebra equation, terms are separated by an addition sign, subtraction sign or an equal sign. For example,

3a + 7b = 21.

This equation have 3 terms.

(a−b)²+b²/a²

proof

if A is the area of the

inner squared, so A= c², and c²= (a−b)²+b²

so the side of the outer must be a-b +b=a, its area is a²

Unordered polynomial is

7x3y3 + 4 - 11x5y2 - 3x2y

Polynomial in descending order looks like this

-11x5y2 + 7x3y3 - 3x2y + 4

Degree of the second term is 5 ( because of x5 )

Which of the following is a factor of 2x4 + 22x3 + 60x2? 2x3 x4 x + 4 x + 5

The correct answer is **Option D, **or **X+5**. I hope I answered this question to your satisfaction Have a nice day!

► For instance, the quadratic equation:

x² – (6 + 4i)x + (9 + 12i) = 0

has for discriminant:

Δ = (6 + 4i)² – 4(9 + 12i) = 36 – 16 + 48i – 36 – 48i = -16

which is indeed negative.

Its solutions will then be:

x₁ = [(6 + 4i) + 4i]/2 = 3 + 4i

x₂ = [(6 + 4i) – 4i]/2 = 3

And the other solution here is 3.

► If you are not convinced, the quadratic equation:

x² – (6 + 5i)x + (5 + 15i) = 0

has for discriminant:

Δ = (6 + 5i)² – 4(5 + 15i) = 36 – 25 + 60i – 20 – 60i = -9

which is indeed negative.

Its solutions will then be:

x₁ = [(6 + 5i) + 3i]/2 = 3 + 4i

x₂ = [(6 + 5i) – 3i]/2 = 3 + i

And the other solution here is 3+i.

► In fact, every quadratic equation of the form:

x² – [6 + (4 + α)i]x + (3 + 4i)(3 + αi) = 0

where α is any real, has for discriminant:

Δ = [6 + (4 + α)i]² – 4(3 + 4i)(3 + αi)

= 36 – (4 + α)² + 12(4 + α)i – 36 + 16α – 12(4 + α)i

= 16α – (4 + α)²

= 16α – 16 – 8α – α²

= -16 + 8α – α²

= -(α – 4)²

WILL be negative.

Their solutions will then be:

x₁ = [ [6 + (4 + α)i] – (α – 4)i ]/2 = 3 + 4i

x₂ = [ [6 + (4 + α)i] + (α – 4)i ]/2 = 3 + αi

And the other solution will then be is 3+αi.

Since α can take any real value, you'll obtain an infinity of solutions of the form 3+αi.

► So conclusively:

If the discriminant of a quadratic is negative AND one of the solutions is 3+4i, the only thing we can say about the other solution is that its real part must be 3.

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

**If ST = 21, SP = 3b – 11, and PT = b + 4, the value of b would be 14.**

I hope my answer has come to your help. God bless and have a nice day ahead!

First one looks like you are squaring the number, then multiplying the result by 4, i.e.

y=4x2

second one is similar, but instead of squaring and multiplying by 4, you are squaring and then dividing by 2

I hope my answer has come to your help. God bless and have a nice day ahead!

is as follows

mean=13(.5)=6.5

variance=6.5(.5)=3.25

Pr[fewer than 4]=

Pr[N<=3] Apply the continuity correction

Pr[N<=3.5]~=Pr[Z<3.5-6.5/sqrt(3.25)]=

Pr[Z<-1.66]=0.048457226

I hope my answer has come to your help. God bless and have a nice day ahead!

A = (x+3)^2 = x^2+6x+9

$70 - $49 = 21

Now we find out what percent $21 is of $70.

21/70 × 100 = 30%.

That means the discount is 30%!

Now we must find 30% of $100, which is $30.

Then we subtract $30 from $100.

**$100 - $30 = 70$**

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

6 times the square root of 2.25 and then minis 4.23 =

________________

6√(2.25) - 4.23 = ?

__________________

6√(2.25) - 4.23 =

______________________

6*(1.5) - 4.23 =

_______________

9 - 4.23 =

_______________

4.77

Now we'll plug in the numbers they give us into the formula:

y-4= 0(x+2).

Which solution for the value of x in the figure below is incorrect? Explain.

When RHS is brought to the LHS

Subtraction and not addition should be done to find the solution for x.

I hope my answer has come to your help. God bless and have a nice day ahead!

**1) The answer is: [B]: r = 5 .**

**__________________________**

**Explanation:**

**___________**_______________

Given: 7r − 7 = 2r + 18 ; Round your answer to the nearest tenth, if necessary.

____________________________

Since "r" is the only variable given, let us assume we want to solve for "r" (instead of "x").

___________________________

→ Subtract "2r" from EACH SIDE of the equation; and & add "7" to EACH SIDE of the equation:

_____________

→ 7r − 7 − 2r + 7 = 2r + 18 − 2r + 7 ; to get: → 5r = 25 ;

_____________

→ Now, divide EACH SIDE of the equation by "5"; to isolate "r" on one side of the equation; and to solve for "r" :

______________

→ 5r / 5 = 25 / 5 → r = 5 → which is: "Answer choice: [B]".

_________________

**Let us check our answer, by plugging in "5" for "r" in the original equation:**

_________________

→ 7r − 7 = 2r + 18 ; → 7(5) − 7 =? 2(5) + 18? ;

______________________

→ 35 − 7 =? 10 + 18 ?; → 28 =? 28? Yes!

______________________

**2) The answer is: [D]: x = 2 .**

**_____________**

**Explanation:**

_____________

Given: 2x + 12 = 18 − x ; Solve for "x" (round to nearest tenth, if necessary).

_______________

→ Add "x" to EACH SIDE of the equation, & subtract "12" from EACH SIDE of the equation: → 2x + 12 + x − 12 = 18 − x + x − 12 ;

______________

→ To get: 3x = 6 ; → Divide EACH SIDE of the equation by "3";

to isolate "x" on one side of the equation; and to solve for "x":

_____________

→ 3x / 3 = 6 / 3 ; → x = 2 ; which is: "Answer choice: [D]".

______________

**Let us check our answer, by plugging in "2" for "x" in the original equation:**

________________

→ 2x + 12 = 18 − x ; → 2(2) + 12 =? 18 − 2 ?

________________

→ 4 + 12 =? 18 − 2 ? ; → 16 =? 16? Yes!

________________________________

**3) The answer is: [A]: x = -3 .**

**_____________**

**Explanation:**

________________

Given: 8x − 3 = 15x + 18 ; Solve for "x". Round your answer to the nearest tenth, if necessary.

_________________

→ Subtract "8x" from EACH SIDE of the equation, & add "3" to EACH SIDE of the equation:

_______________

→ 8x − 3 − 8x + 3 = 15x + 18 − 8x + 3 ; to get:

_______________

→ 0 = 7x + 21 ; → Subtract "21" from EACH SIDE of the equation;

_______________

→ 0 − 21 = 7x + 21 − 21 ; to get:

_______________

→ -21 = 7x ; Now divide EACH SIDE of the equation by "7";

to isolate "x" on one side of the equation; & to solve for "x":

_______________

→ = -21 / 7 = 7x / 7 ; → -3 = x ; which is "Answer choice: [A]."

**_________________**

**Let us check our answer, by plugging in "-3" for "x" in the original equation:**

________________

→ 8x − 3 = 15x + 18 ; → 8(-3) − 3 =? 15(-3) + 18 ?;

________________________

→ -24 − 3 =? -45 + 18 ? ; → -27 =? -27? Yes!

**___________________________**

**4) The answer is: [C]: y = 11 .**

**_____________**

**Explanation:**

**____________**

Given: 6y − 6 = 4y + 16 ; Solve for "y"; Round to the nearest tenth, if necessary.

____________

(Note: Since "y" is the only variable given; assume we are to solve for "y" instead of "x").

____________

→ Subtract "4y" from EACH SIDE of the equation, & add "6" to EACH SIDE of the equation; → 6y − 6 − 4y + 6 = 4y + 16 − 4y + 6 ; to get:

_______________

→ 2y = 22 ; Now, divide EACH SIDE of the equation by "2"; to isolate "y" one side of the equation; and to solve for "y" ;

_______________

→ 2y / 2 = 22 / 2 ; → y = 11 → which is "Answer choice: [C]".

**_______________________________**

**Let us check our answer, by plugging in "11" for "y" in the original equation:**

**___________________**

→ 6y − 6 = 4y + 16 ; → 6(11) − 6 =? 4(11) + 16 ?

_______________________

→ 66 − 6 =? 44 + 16 ? → 60 =? 60 ? Yes!

**__________________**

**5) The answer is: [B]: x = -11 .**

**_____________________**

**Explanation:**

**_________________**

Given: 3(x − 4) = 5(x + 2) ; Solve for "x". Round to the nearest tenth, if necessary.

**___________**

**→Note the "distributive property of multiplication":**

**_____________**

**a*(b + c) = ab + ac ; and: a*(b − c) = ab − ac ;**

**_______________**

→ Let us expand EACH SIDE of our given equation.

→Start with the "left-hand side":

____________

3(x − 4) = (3*x) − (3*4) = 3x − 12;

______________________________

→Now let us expand the "right-hand side" of the given equation:

____________

→ 5(x + 2) = (5*x) + (5*2) = 5x + 10 ;

______________

→Now, we can rewrite the original equation:

_______________

→ 3(x − 4) = 5(x + 2) ; by substituting the expanded values for EACH SIDE of the question: → 3x − 12 = 5x + 10 ;

__________________

→ Subtract "3x" from EACH SIDE of the equation; and add "12" to EACH SIDE of the equation: → 3x − 12 − 3x + 12 = 5x + 10 − 3x + 12 ; to get:

________________

→ 0 = 2x + 22; → Now subtract "22" from EACH SIDE of the equation:

______________

→ 0 − 22 = 2x + 22 − 22 ; to get: → -22 = 2x ;

__________

→ Divide EACH SIDE of the equation by "2"; to isolate "x" on one side of the equation; & to solve for "x" ;

_____________

→ -22 / 2 = 2x /2 ; → -11 = x ; which is "Answer choice: [B]".

______________

**Let us check our answer, by plugging in "-11" for "x" in the original equation:**

**___________**

→ 3(x − 4) = 5(x + 2) ; → 3(-11 − 4) =? 5(-11 + 2) ? ;

_______________________

→3(-15) =? 5(-9) ? ; → -45 =? -45 ? Yes!

**_____________________________________________**

**Hope these answers and explanations are helpful. Best of luck!**

## Use our writing service to score better and meet your deadlines

Solve for w. 2w=12-4w Simplify your answer as much as possible.

2w=12-4w

Firstly, let's simplify, and divide all terms by 2:

w=6-2w

Now, we add 2w over to the other side:

3w=6

And finally, we divide both sides by 3:

w=2

Hope this helps!

f ( x ) = √( 1 - x²), g ( x ) = - 2

= - 50/3

My = p ∫ x * ( f ( x ) ) dx

My = p ∫ x ( √(1+x²)) dx

Substitution: 1 - x² = u, x dx = - du/2

**M x = - 50/3, M y = 0**

M ≈ 5 * 6.3 ≈ 31.2

x = M y / M = 0 / 31.5 = 0

y = M x / M = -50/3 : 31.5 ≈ - 0.529

The center of mass is

**( 0, -0.529 )**

we have

Combine like terms

therefore

__the answer is the option C__

He combined the terms and incorrectly

Find the value of 3x + 2 when 7+ x = 5

x= 5-7

x= -2

3.(-2)+2

-6+2

-4

## Use our writing service to score better and meet your deadlines

What is the answer for 5(n-6)-2=2n-5

5n-30-2 = 2n-5

5n - 2n = 30+2-5

3n = 27

n = 27/3

n = 9

**So, your final answer is 9**

Hope this helps!

Is 50 tens 9 ones <,>,= 49 tens 35 ones

Find all the zeros of the function y=x^3+6x^2+x+6

one more thing X= not real solution

Graph passes through the point (-1, 0).

Therefore, x = -1 and y = 0.

This is the only equation which is true for x = -1 and y = 0.

Therefore, the solution is